Assessment of pulmonary mechanical properties influence on patternsand indices of their ventilation mechanics in various biologicalconditions - A. I. Karzilov; F. F. Tetenev; T. N. Bodrova (Бюллетень сибирской медицины, 2007)
Patterns and mechanics of pulmonary ventilation are studied in sharp experiment on living rabbits (n = 15), after their sacrificing (n = 15) and on isolated lungs (n = 7). The data obtained revealed that mechanical properties of lungs and thorax - pulmonary integrity influence on forming patterns and parameters of lung mechanics during their ventilation independently regulatory influences of living organism. Classical Donders model of lung operation is incorrect for considering mechanical processes of lung ventilation because it take into account influence of mechanical lung properties and a thorax on forming patterns and parameters of ventilation mechanics.